Effect of seed layer on optical properties and visible photoresponse of ZnO/Cu2O composite thin films. Issue 10 (December 2015) - Lv, Jianguo; Xu, Jinhua; Zhao, Min; Yan, Pengpeng; Mao, Sicong; Shang, Fengjiao; He, Gang; Zhang, Miao; Sun, Zhaoqi
Abstract: ZnO/Cu2 O composite thin films were deposited on Cu foil using a simple solution method with a variety of ZnO seed layers inserted between the Cu2 O and ZnO layers. Effects of the ZnO seed layers on the microstructure, optical properties and photoresponse of the thin films were investigated. The intensity of the ZnO (002) diffraction peak increases with increasing thickness of the seed layer. Dissolution of ZnO nanoparticles also occurs during growth of the ZnO thin films. The optical band gap of the Cu2 O layer decreases gradually from 1.86 to 1.66 eV as the thickness of the ZnO seed layer increases. Change of the optical band gap could be attributed to Cu 2+ impurities in the Cu2 O and (or) ZnO layers. A visible emission from sample with a seed layer of four times can be attributed to phonon-assisted exciton recombination in Cu2 O. An ultraviolet emission centered at 380 nm and a broad visible emission band is observed in the two samples with a seed layer of six and eight times. The best photoresponse performance has been observed in the sample with a seed layer of eight times. This is likely a result of the stronger visible absorption and better band alignment in samples, which facilitates electron transfer from the conduction band of Cu2 O to the conduction band of ZnO.